ANALISIS KESESUAIAN IMPLEMENTASI PROGRAM GERAKAN LITERASI DI SEKOLAH BERDASARKAN DESAIN INDUK GERAKAN LITERASI SEKOLAH (STUDI KASUS DI SMA NEGERI 2 BLITAR) - Almer Samantha Hidaya; Syifaun Nafisah (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2022)
The School Literacy Movement is a person's ability to access, understand, and use information and media intelligently. This movement is an effort to make schools educational institutions so that students are literate. The regulation of the main design of this movement is in Design of the School Literacy Movement. This study aims to determine the suitability of implementing the school literacy movement program based on the guidelines in the Master Design of the School Literacy Movement. This research is a mixed method research with quantitative and qualitative approaches. The data-collecting methods are interviews, observation, and documentation at SMA Negeri 2 Blitar. To analyze the data used, Milles and Huberman's theory through 3 steps; data reduction, data presentation, and conclusion. The validity test in this research uses triangulation and member checks. The decision of the study is the implementation of the School Literacy Action program in SMA Negeri 2 Blitar generally was appropriate with the Main Design of School Literacy Action. SMA Negeri 2 Blitar has implemented most of the program of school literacy criteria in the physical environment, socio-affective environment, academic environment, and stage of development. The achievement of implementing the School Literacy Action program in SMA Negeri 2 Blitar was 90,63 %. The researcher suggests that it needs to provide books and reading materials for the student's parents or visitors in the school environment, except classrooms, such as corridors and the head's office, and determine some required books to be read by the school members. Moreover, schools should give special attention to the XII grade students in the second semester and emphasize literacy learning against the awareness of each individual.